2016
DOI: 10.4314/wsa.v42i1.09
|View full text |Cite
|
Sign up to set email alerts
|

Fate, behaviour, and implications of ZnO nanoparticles in a simulated wastewater treatment plant

Abstract: Increased use of engineered nanoparticles (ENPs) has resulted in their entry into municipal wastewater treatment plants (WWTPs) as their final sinks. However, the adverse impact of ENPs on the bacterial activity in the activated sludge WWTPs is not yet well understood, despite their increased release into such systems. In this study, the impacts on WWTPS associated with the disposal of zinc oxide (ZnO) ENPs was investigated using a simulated WWTP developed as per the prescribed Organization for Economic Co-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
(61 reference statements)
0
11
2
Order By: Relevance
“…The exposure to 10 and 50 mg/L ZnO NPs further decreased COD removal efficiencies to 72.7% and 65.7%, respectively. This is in disagreement with Chauque et al [25] who reported no effect on COD removal at 20 mg/L ZnO NP. Our findings contradict previous studies of the effects of ZnO NPs on COD removal efficiencies.…”
Section: Effect Of Zno Nps and Zn 2+ Ions On Cod Removalcontrasting
confidence: 80%
See 1 more Smart Citation
“…The exposure to 10 and 50 mg/L ZnO NPs further decreased COD removal efficiencies to 72.7% and 65.7%, respectively. This is in disagreement with Chauque et al [25] who reported no effect on COD removal at 20 mg/L ZnO NP. Our findings contradict previous studies of the effects of ZnO NPs on COD removal efficiencies.…”
Section: Effect Of Zno Nps and Zn 2+ Ions On Cod Removalcontrasting
confidence: 80%
“…Less Zn 2+ was released from NP because humic acids are known to stabilize ZnO NP and retard dissolution rates. [25] By comparison, in a recent study on the fate and behaviour of ZnO NPs in a simulated WWTP, Musee et al [17] reported an effluent Zn concentration of 1.39 mg/L after 240 hours of exposure. In the present study at 5 hours exposure, 86.3%, 85.1% and 85.8% of zinc from ZnO NPs were retained in the sludge at initial ZnO concentrations of 1.0, 10 and 50 mg/L respectively, showing that a large fraction of the ZnO NPs was removed from the wastewater due to adsorption onto waste activated sludge.…”
Section: Removal Of Zno Nps and Zinc Ions In The Activated Sludge Promentioning
confidence: 98%
“…Nanoparticles (NPs) have always existed in the natural environment (soil, water and atmosphere) 1 . Although exposure to NPs is not a new phenomenon, the rapid development of commercial applications, involving the use of a large variety of engineering NPs, has resulted in the introduction of quite higher amounts into the environment 2 . Engineering NPs have been found in wastewater, which are directed to treatment plants, and then discharged, in the aquatic environment 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A continuous supply of NPs in a system may have a major impact on its living organisms (fungi, algae, bacteria, and protozoa) and eventually in the system operation performance. Although WWTPs are the main recipients of NPs and many studies have been performed on the effects of NPs on various organisms, the adverse effects of NPs on bacterial populations in activated sludge need further investigation [5]. Sorption of pollutants on activated sludge is among the main processes for toxic substances removal in wastewater, such as metals, synthetic organic chemicals, suspended solids, and pathogens [6], including NPs.…”
Section: Introductionmentioning
confidence: 99%